Cluster-based pre-scaling up of tomato technologies in harari region rural areas: Small holder farmers livelihood improvement - Ibsa Aliyi Usmane; Abdulaziz Teha; Badaso Urgesa; Oromiya Magarsa; Robe Elema (Open Journal of Plant Science - Peertechz Publications, 2020)
Small-holder farmers' livelihoods basically depend on agricultural products and other related activities. Based on this impression, Agricultural Extension Research team conducted cluster-based pre-scaling up of improved tomato variety (Malka shola) at Harari region in two kebeles (Aradas) Kile and Dodota with objectives of scale up the improved Tomato technologies for increasing the production and productivity for the improvement of small-scale farmers livelihood and strengthen the linkages among stakeholders on the promotion of tomato technologies for one year (2019/2020). For this research activity, 100 farmers with 40% (pre-harvest to post harvest) women composition were participated by grouping them in three clusters, from land preparation to marketing of their products. As a result, 21.88ton/ha at cluster1 12.37ton/ha at cluster 2 and 14.59ton/ha at cluster 3 were produced from the total 75 hectares of land by irrigation system at off season in which Agricultural Extension Research team provided all necessary inputs to targeted farmers according to the land size they own and know how. Throughout this research activity implementation the disease occurrence, ups and down of market price, shortage of seed supply and non-frequent advices from immediate local development agents were raised by farmers as challenges. Therefore, research institutes, government's development organizations, NGOs, and other stakeholders should jointly focus on plant protection, market linkage strengthening, facilitation, capacitating, monitoring and evaluate on ground situation at field and farmers level.